Opening Remarks from the Feed the Future Nutrition Innovation Lab. - Thorne-Lyman, Andrew. (Tufts University. Tisch Library., 2017)
Andrew Throne-Lyman welcomes dignitaries and guests to the 5th Annual Scientific Symposium providing some history and statistics about the history of the symposium.